Nanoprobe-Based Near-Infrared II Optical Imaging for Guiding Precision Glioma Therapy - Dong L; Li W; Li L; Xue X; Liu X; Hu C (International Journal of Nanomedicine)
Liang Dong,1,* Wenzhong Li,1,* Lulu Li,2 Xiaobo Xue,1 Xiaojie Liu,1 Changchen Hu1 1Department of Neurosurgery, Shanxi Provincial People’ s Hospital,Shanxi Medical University, Taiyuan, Shanxi, 030012, People’ s Republic of China; 2Department of First Clinical Medicine, Shanxi Medical University, Taiyuan, Shanxi, 030012, People’ s Republic of China*These authors contributed equally to this workCorrespondence: Changchen Hu, Department of Neurosurgery, Shanxi Provincial People’ s Hospital, Shanxi Medical University, Taiyuan, Shanxi, 030012, People’ s Republic of China, Email hucc88@sxmu.edu.cnAbstract: Glioma is a heterogeneous primary and metastatic tumour of the central nervous system that is highly invasive and destructive, with a poor prognosis and low survival rate. Near-infrared II (NIR-II) fluorescence imaging has revealed significant potential for advancing glioma diagnosis because of its non-invasiveness, high spatiotemporal resolution, reasonable sensitivity, and deep penetration. These imaging techniques have been widely used to guide real-time glioma treatment with high accuracy and efficiency. This review summarised the applications and progress of NIR-II in guiding glioma surgery, targeted drug delivery, photoacoustic therapy, and multimodal therapy. We demonstrated the feasibility and practicality of integrating these technologies into glioma diagnosis and treatment. These technologies have great potential to improve patient prognosis further. Furthermore, this review highlights the challenges of using these technologies in future clinical studies.Keywords: near-infrared II, glioma, surgery, multimodal therapy, phototherapy